The Impact Of Applied Linguistics On The Field Of Grammar: A Comparative Analytical Study With The Letter 'و' (Waw) As A Model/ أثر اللغويات التطبيقية في علم النحو: حرف الواو أنموذجًا دراسة تحليلية مقارنة - Yaseen, Mohammed Abdulkareem (Ijaz Arabi Journal of Arabic Learning, 2024)
Language serves as a crucial tool for human interaction. It transcends its basic structure of words, rules, and syntax, reflecting the complex subtleties of culture, history, and the social development of its users. Within the study of language, applied linguistics stands out as an essential discipline that delves deeper than theoretical discussions. It critically examines how language is utilized, its manifestations in various contexts, and its multifaceted applications in human communications across different fields. Central to this research is the exploration of applied linguistics's transformative influence on the grammar domain. This study emphasizes the Arabic letter 'و) 'Waw). Given its frequent occurrence and versatile role in texts, ranging from the esteemed Quran to classical Arabic literature and detailed grammatical discussions, the comprehensive and precise understanding of the letter 'و 'is paramount. Such understanding facilitates both rigorous textual analysis and profound comprehension of linguistic constructs within the Arabic language. This research adopts a comparative methodology to discern the depth of this influence. It juxtaposes the time-honored traditional grammatical approaches with contemporary perspectives offered by applied linguistics. Through this comparative lens, the study sets out to achieve two primary objectives: firstly, to identify how applied linguistics might present alternative or even more enriched interpretations of 'و 'distinct from classical views, and secondly, to elucidate the tangible implications of these interpretations in practical, real-world linguistic applications. In culmination, this rigorous investigation serves a dual purpose. It sheds light on the nuanced roles and interpretations of the Arabic letter, 'و ', and positions applied linguistics as a beacon guiding the future trajectory of grammatical studies. The research accentuates the indispensability of a symbiotic relationship between traditional grammar and modern applied linguistic techniques, advocating for their combined use in achieving a holistic and evolved understanding of the dynamic Arabic language system.